Parent and child co‐resident status among an Australian community‐based sample of methamphetamine smokers. (8th September 2020) - Ward, Bernadette; Kippen, Rebecca; Reupert, Andrea; Maybery, Darryl; Agius, Paul A.; Quinn, Brendan; Jenkinson, Rebecca; Hickman, Matthew; Sutton, Keith; Goldsmith, Rachael; Dietze, Paul M.
Abstract: Introduction: Children in families where there is substance misuse are at high risk of being removed from their parents' care. This study describes the characteristics of a community sample of parents who primarily smoke methamphetamine and their child or children's residential status. Design and Methods: Baseline data from a prospective study of methamphetamine smokers ('VMAX'). Participants were recruited via convenience, respondent‐driven and snowball sampling. Univariable and multivariable logistic regression analyses were used to estimate associations between parental status; fathers' or mothers' socio‐demographic, psychosocial, mental health, alcohol, methamphetamine use dependence, alcohol use and child or children's co‐residential status. Results: Of the 744 participants, 394 (53%) reported being parents; 76% (88% of fathers, 57% of mothers) reported no co‐resident children. Compared to parents without co‐resident children, parents with co‐resident children were more likely to have a higher income. Fathers with co‐resident children were more likely to be partnered and not to have experienced violence in the previous 6 months. Mothers with co‐resident children were less likely to have been homeless recently or to have accessed treatment for methamphetamine use. Discussion and Conclusions: The prevalence of non‐co‐resident children was much higher than previously reported in studies of parents who use methamphetamine; irrespective of whether in or out of treatment. There is a need for accessible support and services for parents who use methamphetamine; irrespective of their child or children's co‐residency status. Research is needed to determine the longitudinal impact of methamphetamine use on parents' and children's wellbeing and to identify how parents with co‐resident children (particularly mothers) can be supported.